An exploration into the effect of leadership behaviour of principals on school culture in selected international schools in South East Asia - Langridge, Christopher (2016)
This study investigates the links between the leadership of school principals and school culture in international schools in South East Asia. Two main research questions shaped the study: i) To what extent, if at all, do the principals exhibit behaviours of transformational leadership? ii) How does the selected transformational principal’s leadership style and behaviour affect the culture of the schools?